Bcl2‐Expressing Quiescent Type B Neural Stem Cells in the Ventricular–Subventricular Zone Are Resistant to Concurrent Temozolomide/X‐Irradiation. (17th October 2019) - Cameron, Brent D.; Traver, Geri; Roland, Joseph T.; Brockman, Asa A.; Dean, Daniel; Johnson, Levi; Boyd, Kelli; Ihrie, Rebecca A.; Freeman, Michael L.
Abstract: The ventricular–subventricular zone (V‐SVZ) of the mammalian brain is a site of adult neurogenesis. Within the V‐SVZ reside type B neural stem cells (NSCs) and type A neuroblasts. The V‐SVZ is also a primary site for very aggressive glioblastoma (GBM). Standard‐of‐care therapy for GBM consists of safe maximum resection, concurrent temozolomide (TMZ), and X‐irradiation (XRT), followed by adjuvant TMZ therapy. The question of how this therapy impacts neurogenesis is not well understood and is of fundamental importance as normal tissue tolerance is a limiting factor. Here, we studied the effects of concurrent TMZ/XRT followed by adjuvant TMZ on type B stem cells and type A neuroblasts of the V‐SVZ in C57BL/6 mice. We found that chemoradiation induced an apoptotic response in type A neuroblasts, as marked by cleavage of caspase 3, but not in NSCs, and that A cells within the V‐SVZ were repopulated given sufficient recovery time. 53BP1 foci formation and resolution was used to assess the repair of DNA double‐strand breaks. Remarkably, the repair was the same in type B and type A cells. While Bax expression was the same for type A or B cells, antiapoptotic Bcl2 and Mcl1 expression was significantly greater in NSCs. Thus, the resistance of type B NSCs to TMZ/XRT appears to be due, in part, to high basal expression of antiapoptotic proteins compared with type A cells. This preclinical research, demonstrating that murine NSCs residing in the V‐SVZ are tolerant of standard chemoradiation therapy, supports a dose escalation strategy for treatment of GBM. Stem Cells 2019;37:1629–1639 Abstract : The brain's ventricular–subventricular zone is a site of type B neural stem cell‐mediated neurogenesis and unfortunately for very aggressive glioblastoma. Treatment for glioblastoma consists of resection, concurrent temozolomide, and X‐irradiation, followed by adjuvant temozolomide. We show that concurrent temozolomide/X‐irradiation followed by adjuvant temozolomide induces apoptosis in type A neuroblasts. In contrast, quiescent neural stem cells, which express high levels of Bcl2 and Mcl1, survive and repopulate type A neuroblasts.